ANALISIS DETERMINAN PRODUKSI LABU MADU DALAM UPAYA MENINGKATKAN PENDAPATAN PETANI LABU MADU KABUPATEN MUARO JAMBI (STUDI KASUS DESA PUDAK) - Yolanda, Dela; Dani, Rian; Putra, Adi; Affriza, Muhammad; Al Munawaroh, Azizah (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
This research aims to analyze the determinants of honey pumpkin production in an effort to increase the income of honey pumpkin farmers in Muaro Jambi district (case study of Pudak village). The research method used in this research is a qualitative research method. A survey is collecting information from a portion of the population (sample) in the hope of getting fairly representative information. Meanwhile, quantitative uses data collection techniques from a sample of 29 farmers. Multiple linear regression analysis was used to answer the second research objective, namely what factors influence honey gourd production in Pudak Village, Muaro Jambi Regency. Capital and labor variables have a significant and positive effect on honey pumpkin production. Meanwhile, technological variables do not have a significant effect on honey pumpkin production. Production variables have a significant effect on the income of honey pumpkin farmers.